Doxycycline Inducible Chimeric Antigen Receptor T Cells Targeting CD147 for Hepatocellular Carcinoma Therapy - Zhang, Ren-Yu; Wei, Ding; Liu, Ze-Kun; Yong, Yu-Le; Wei, Wei; Zhang, Zhi-Yun; Lv, Jian-Jun; Zhang, Zhao; Chen, Zhi-Nan; Bian, Huijie (Frontiers in Cell and Developmental Biology, 2019)
Chimeric antigen receptor T cell (CAR-T) therapy to hematological malignancies has demonstrated tremendous clinical outcomes. However, the therapeutic efficacy of CAR-T cells in solid tumor remains limited due to the scarcity of tumor-specific antigen targets and the poor infiltration of CAR-T cells into tumor tissue. In this study, we developed a novel inducible CAR-T cell system which targets CD147, a tumor-associated antigen for hepatocellular carcinoma (HCC). To minimize potential toxicities of CAR-T cell therapy, the Tet-On 3G system was introduced to induce CD147CAR expression in a right place at a right time. Specifically, Tet-CD147CAR lentiviral vector (LV-Tet-CD147CAR) was constructed which comprised of CD147CAR controlled by Tet-On system. Tet-CD147CART cells were successfully generated from activated T cells by infection with LV-Tet-CD147CAR. Proliferation, cytotoxicity, and cytokines secretion of Tet-CD147CART cells were significantly increased against CD147-positive cancer cells in the presence of doxycycline (Dox), compared to that of Tet-CD147CART cells in the absence of Dox and PBMCs. Consistently, in vivo studies indicated that the tumor growth in nude mice was significantly inhibited by (Dox+) Tet-CD147CART cells through multiple intratumoral administration. Taken together, our results indicated that the expression and activity of CD147CAR were controlled by Dox both in vitro and in vivo, which facilitated decreased toxicity and adverse effects to CAR-T cell therapy. Moreover, this study provides viable evidences in support of the potential benefits and translation of this CAR-T cells targeting CD147 strategy for the treatment of patients with HCC.